Pembuatan Direktori Perguruan Tinggi Negeri dan Swasta di Kota Padang - Ernita, Peni; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThe writing of this paper discusses the creation of a directory of public and private universities in the city of Padang. The purpose of writing this paper is to facilitate the search for public and private university directories in the city of Padang. The method used in the preparation of this paper is descriptive method. Data collection techniques were carried out by direct observation and literature study.Based on the discussion it can be concluded as follows; first, techniques in making directory of state and private universities in the city of Padang; (a) data collection of state and private universities throughout the City of Padang; (b) compiling the directory concept; (c) determine the subject; (d) classification or grouping of data; (e) cover design; (f) directory preparation. Second, the obstacles in making the directory of state and private universities in Padang City are as follows: (a) in the search for locations, there are many locations of universities that have changed places, functions and even those that are no longer active; (b) it takes a long time to create this directory; (c) making a location plan has difficulty because there are several locations where the information about the road to the location is unclear and does not understand the condition of the road; Third, the efforts made in overcoming the constraints of making a directory of state and private universities in Padang City are: (a) searching for locations that have moved places, functions or which are no longer active by making direct observations to the location in order to ensure conditions and information about the college; (c) making the directory takes a long time so the writer must be able to arrange the time so that the directory products of state and private universities in West Sumatra can be completed at the specified time; (c) overcome the difficulty of making the location plan of the writer using the help from google maps and information from the surrounding community.Keywords: directory,Â Universities, City of Padang